Comparison of Conjugates Obtained Using DMSO and DMF as Solvents in the Production of Polyclonal Antibodies and ELISA Development: A Case Study on Bisphenol A - Anna N. Berlina; Nadezhda S. Komova; Kseniya V. Serebrennikova; Anatoly V. Zherdev; Boris B. Dzantiev (Antibodies)
When developing immunochemical test systems, it is necessary to obtain specific antibodies. Their quality depends, among other things, on the immunogen used. When preparing hapten–protein conjugates to obtain antibodies for low-molecular-weight compounds, the key factors are the structure of the hapten itself, the presence of a spacer, the size of the carrier protein and the degree of its modification by hapten molecules. This work shows that one additional factor—the conditions for obtaining the hapten–protein conjugate—is overlooked. In this work, we have synthesized conjugates of bisphenol A derivative 4,4-bis(hydroxyphenyl)valeric acid (BVA), the protein carrier soybean trypsin inhibitor (STI), and bovine serum albumin (BSA) in reaction media combining water with two organic solvents: dimethylformamide (DMF) or dimethyl sulfoxide (DMSO). Namely, BSADMF–BVA, STIDMF–BVA, BSADMSO–BVA and STIDMSO–BVA conjugates were obtained. Rabbit polyclonal antibodies against the BSADMF–BVA conjugate demonstrated basically different interactions in the developed ELISA systems using either STIDMF–BVA or STIDMSO–BVA conjugates. The use of the STIDMF–BVA conjugate demonstrated the absence of competition in combination with antisera obtained from BSADMF–BVA in an ELISA. A competitive interaction was observed only with the use of the STIDMSO–BVA conjugate. Under the selected conditions, the detection limit of bisphenol A was 8.3 ng/mL, and the working range of determined concentrations was 18.5–290.3 ng/mL. The obtained data demonstrate the possibility of achieving sensitive immunoassays by simply varying the reaction media for the hapten–protein conjugation, which could provide an additional tool in the development of immunoassays for other low-molecular-weight compounds.